Court testimony : an introduction - Tulalian, Victor T. (Philippines : Wisemans Books Trading, 2021)
"This book contains introductory course on the subject (3z(BCourt Testimony.(3y (BIt does not aim to convert the readers into (3z(Blitigators(3y (Bin the mold and caliber of Oscar Finley and Wally Figg of the law firm of Finley & Figg (from John Grisham$1 (Bs novel (3z(BThe Litigators(3y(B)."s
Includes Bibliographical references.
English text.
Keywords: Witness Testimony